Candid Creatures : How Camera Traps Reveal the Mysteries of Nature - Kays, Roland, 1971- (Book collections on Project MUSE., 2016)
In Candid Creatures, the first major book to reveal the secret lives of animals through motion-sensitive game cameras, biologist Roland Kays has assembled over 600 remarkable photographs. Drawing from archives of millions of color and night-vision photographs collected by hundreds of researchers, Kays has selected images that show the unique perspectives of wildlife from throughout the world. Using these photos, he tells the stories of scientific discoveries that camera traps have enabled, such as living proof of species thought to have been extinct and details of predator-prey interactions. Each image captures a moment frozen in the camera's flash as animals move through their wild habitats. Kays also discusses how scientists use camera traps to address conservation issues, creating solutions that allow humans and wild animals to coexist. More than just a collection of amazing animal pictures, the book's text, maps, and illustrations work together to describe the latest findings in the fast-moving field of wildlife research. Candid Creatures is a testament to how the explosion of game cameras around the world has revolutionized the study of animal ecology. The powerful combination of pictures and stories of discovery will fascinate anyone interested in science, nature, wildlife biology, or photography.